Improving Power Grid Resilience Under Extreme Weather Conditions With Proper Regulation and Management of DERs—Experiences Learned From the 2021 Texas Power Crisis - Pan, Weiqi; Li, Yang (Frontiers in Energy Research, 2022)
Due to climate change in the past few decades, extreme weather conditions have become more frequent and caused power outages with enormous damage to the well-being and the economy. Affected by extremely cold weather, the 2021 Texas power crisis deployed the most significant firm load shedding in US history, costing the economy 10 billion to 20 billion via direct and indirect loss. The North American Electric Reliability Organization (NERC), Federal Energy Commission (FERC), and other literature studies conducted post-event analysis from the perspective of conventional power systems’ planning and operation, and little discussion was made on the distributed energy resources (DERs). Based on the actual data on the 2021 Texas power crisis, this study analyzed the role of DERs in this event and showed the importance of effective regulation and management in improving power grid resilience under such extreme weather conditions.